Left ventricular torsion in primary chronic mitral regurgitation. Issue 5 (19th September 2007) - Borg, A N; Harrison, J L; Argyle, R A; Ray, S G
Abstract : Background: Torsion is essential for normal systolic and diastolic function of the left ventricle (LV), and is known to be abnormal in animal models of mitral regurgitation (MR). There are no comparable data in humans. Objectives: To study LV torsion in humans with chronic primary MR using speckle-tracking echocardiography. Methods: Rotation and rotation rate were measured from two-dimensional (2D) greyscale LV base and apex short-axis images by speckle-tracking echocardiography in 38 patients and 30 controls. Using custom software, plots of torsion against time were constructed by deducting base rotation from apex rotation. Loops of torsion against LV radial/longitudinal displacement and volume were automatically plotted. Results: Peak systolic torsion, systolic torsional velocity and untwisting velocity were similar in the two groups. In controls, untwisting started 23 ms before aortic valve closure but was delayed in MR to 15 ms after aortic valve closure, p<0.001. In normal subjects there was rapid untwisting during isovolumic relaxation, with minimal expansion of the LV radial and longitudinal axes. In MR, early untwisting rate was decreased, with less untwisting for a given volume increase. Extensive LV remodelling and worsening MR were associated with progressive reductions in systolic torsion and untwisting velocity, and progressive delay in the onset of untwisting. Conclusions: Chronic MR results in significant delay and slowing of LV untwisting, such that early untwisting is coupled with chamber expansion. Correlations between disease severity and torsional parameters suggest a potential role of these variables in assessing early signs of ventricular dysfunction.